Peningkatan Kecerdasan Linguistik dengan Bermain Tebak Nama pada Anak Usia 5-6 Tahun - Atika Dhini Insani Nasution; Diah Juliani; Dilia Meilandry; Nabila Nabila; Rezky Aprilia; Masganti Sitorus (Journal on Education, 2023)
Linguistic intelligence is the ability to use language both orally and in writing. In playing guess the name, children can look for objects that are nearby, and can mention the names of animals when their characteristics are mentioned. With linguistic intelligence, it is hoped that it can help in the stages of child development. The purpose of this research is to improve the linguistic intelligence of early childhood by playing guess the name at RA PAI Medan. The type of research used is classroom action research. The results showed that there was an increase in children's linguistic intelligence through guessing the name, namely cycle I reached 34%, cycle II reached 75%. The conclusion of this study is the application of name guessing games can improve children's linguistic intelligence.